PENGARUHMODEL PEMBELAJARAN VAK (VISUAL, AUDITORI, KINESTETIK) TERHADAP KEMAMPUAN MENULIS PUISI OLEH SISWA KELAS VIII SMP N. 2 PORSEA TAHUN PEMBELAJARAN 2012/2013 - Fenny Hermina Sitorus (Asas: Jurnal Sastra, 2012)
This study aimed to clarify the effect of the learning model VAK (Visual, Auditory,Kinesthetic) the ability to write poetry by the students of class VIII SMP N.2 PorseaLearning Year 2012/2013. The population of this research is all eighth grade studentsas junior N.2 Porsea 266 people. Samples were taken at random as many as 30people.The method used in this study is an experimental method. The instrument usedis the argument essay writing test. The average value of post-test is 75.50, while forthe pre-test is is 67.1. Thus, it can be said that the average value of students' ability towrite poetry after treatment (post-test) higher than before treatment (pre-test).Hypothesis testing is done by using the test "t". Test hypotheses derived from thecalculation of t = 2.95, then consulted with the table t at 5% significance level = 2.04.Since t = 2.95> t = 2.04 nil then the hypothesis (H) is rejected. It is proved that thelearning model VAK (Visual, Auditory, Kinesthetic) affects the ability to writepoetry class VIII SMP Porsea N.2.Keywords: Effect of the learning model VAK